Corticosteroid therapy for critically ill patients with the Middle East Respiratory Syndrome. - Arabi, Y; Mandourah, Y; Al-Hameed, F; Sindi, A; Al Mekhlafi, G; Hussein, M; Jose, J; Pinto, R; Al-Omari, A; Kharaba, A; Almotairi, A; Al Khatib, K; et al. (American Thoracic Society Journals, 2017)
Rationale Corticosteroid therapy is commonly used among critically ill patients with the Middle East Respiratory Syndrome (MERS), but its impact on outcomes is uncertain. Analyses of observational studies often do not account for patients’ clinical condition at the time of corticosteroid therapy initiation. Objectives To investigate the association of corticosteroid therapy on mortality and on MERS coronavirus RNA clearance in critically ill patients with MERS. Methods MERS ICU patients were included from 14 Saudi Arabian centers between September 2012 and October 2015. We carried out marginal structural modeling to account for baseline and time-varying confounders. Measurements and Main Results Of 309 patients, 151 received corticosteroids. Corticosteroids were initiated at a median of 3.0 days (Quartile Q1, 3: 1.0, 7.0) from ICU admission. Patients who received corticosteroids were more likely to receive invasive ventilation (141/151 [93.4%] vs. 121/158 [76.6%], p≤0.0001) and had higher 90-day crude mortality (112/151 [74.2%] vs. 91/158 [57.6%], p=0.002). Using marginal structural modeling, corticosteroid therapy was not significantly associated with 90-day mortality (adjusted odds ratio 0.75, 95% CI 0.52, 1.07, p=0.12), but was associated with delay in MERS coronavirus RNA clearance (adjusted hazard ratio 0.35, 95% CI: 0.17, 0.72, p=0.005). Conclusions Corticosteroid therapy in patients with MERS was not associated with a difference in mortality after adjustment for time-varying confounders, but was associated with delayed MERS coronavirus RNA clearance. These findings highlight the challenges and importance of adjusting for baseline and time-varying confounders when estimating clinical effects of treatments using observational studies.